Cellular immunotherapies and immune cell depleting therapies in inflammatory bowel diseases: the next magic bullet? - Neurath, Markus; Sands, Bruce Eric; Rieder, Florian (Gut, 2024)
Despite significant advances in biologic and small molecule treatments and the emergence of combination therapies to treat inflammatory bowel diseases (IBD) a large unmet need remains to control intestinal inflammation. New approaches targeting several pathways simultaneously with a favorable safety profile and agents that trigger anti-inflammatory pathways to drive durable resolution of inflammation are needed. This article discusses novel cellular immunotherapies and immune cell depleting therapies in IBD, including CAR-T cell approaches, Tr1 and T regulatory (Treg) cells and cell depleting antibodies such as rosnilimab. These novel approaches have the potential to overcome current therapeutic limitations in the treatment of IBD.
CRIS-Team Scopus Importer:2024-08-02
Keywords: CELLULAR IMMUNOLOGY; IBD CLINICAL